Psychological rehabilitation and re-socialization of persons addicted with psychoactive substances - Lisnovska, L. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article considers the necessity of creating some therapeutic surroundings which is the whole complex of factors, united into the programme and aimed on overcoming dysfunctional display in order to form socially acceptable personal and behavioral qualities of the people which are depended on psycho-active substance. We analyzed specific characteristics of the addicted because after having taken down sharp symptoms the position appeared as the result of the disease is left.
Keywords: people which are depended on psycho-active substance; options; disposition